Restructuring of the e-Learning styles factors for technology training - Din, Rosseni; Kamarulzaman, M Faizal; M Shah, Parilah; Rahman, Saemah; Abdul Karim, Aidah; Omar, Rahilah; Aqsha Lubis, Maimun; Nordin, Mohamad Sahari; Zakaria, M Shanudin; Mastor, Khairul Anwar (IDOSI Publications, 2011)
The introduction of e-training and e-learning in Malaysia was a major step towards the democratisation of many aspects of education for diverse learners. Nevertheless, several surveys of blended or hybrid learning approaches showed some gaps in learning-style research involving the teaching and learning of technology. The initial framework of this study involved the construction of a questionnaire to assess the learning styles of technology trainees who had attended a hybrid e-training course. The questionnaire initially consisted of six factors that assessed learning styles in general. The factors were (i) visual, (ii) kinaesthetic (iii)auditory (iv) tactual, (v) individual and (vi) group-learning styles. The questionnaire was administered to 249 ICT trainers from the Faculty of Education, in one public university in Malaysia. After going through the process of principal-component analysis, learning styles for technology training were eventually classified into five factors with slightly different items and factor names, namely (i) visual, (ii) auditory, (iii) kinaesthetictactual,(iv) individual and (v) group. This paper shows how this process was carried out and further discusses the findings.